2003
DOI: 10.1309/qcuunrmvjy8mwppl
|View full text |Cite
|
Sign up to set email alerts
|

Activated Protein C Resistance Assay Detects Thrombotic Risk Factors Other Than Factor V Leiden

Abstract: Activated protein C (APC) resistance is a common risk factor for venous thromboembolism (VTE) attributed to various mechanisms, including factor V Leiden (FVL) polymorphism. FVL is considered responsible for up to 95% of APC resistance; however, other factor V polymorphisms and elevated factor VIII levels also have been implicated. We assessed whether additional mechanisms contribute to APC resistance in a blinded case-control study of 65 subjects by measuring APC resistance using 3 methods: 2 activated partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 34 publications
0
34
1
Order By: Relevance
“…Previous reports have shown that 5-10 % of APC resistance does not involve FV Leiden [21] whereas in our study this percentage was 38.4 %, increasing the possibility of other inherited or acquired factors contributing towards APC resistance in Indian population like elevated factor VIII levels [22]. Hong Kong and Cambridge gene mutations were absent in all the patients and controls.…”
Section: Discussioncontrasting
confidence: 61%
“…Previous reports have shown that 5-10 % of APC resistance does not involve FV Leiden [21] whereas in our study this percentage was 38.4 %, increasing the possibility of other inherited or acquired factors contributing towards APC resistance in Indian population like elevated factor VIII levels [22]. Hong Kong and Cambridge gene mutations were absent in all the patients and controls.…”
Section: Discussioncontrasting
confidence: 61%
“…[15][16][17][18] Nevertheless, it is probable that use of the aPTT-based assay is still warranted, given that acquired conditions or mutations other than FVL (to which the RVVT assays are quite sensitive) are likely to be important contributors to APCR. 15,19,20 For LA, error rates were also generally < 5%. The error rates in part were dependent on the strength of the LA (higher rates for weaker LA).…”
Section: Discussionmentioning
confidence: 96%
“…A limited repertoire of functional and genetic laboratory assays are currently available for risk assessment. These include FV Leiden [20,21], prothrombin G20210 [22,23], the FXIIIVal34Leu polymorphism [24], FVIII measurements [25], activated protein C resistance assays [26,27] and fibrinogen [28]. These assays, while informative, provide no integrated evaluation of potential stimulus–response coupling.…”
Section: Introductionmentioning
confidence: 99%